Electrical and Magnetic Properties of Polymer Electrolyte (PVA:LiOH) Containing In Situ Dispersed Fe3O4 Nanoparticles. (29th February 2012) - Aji, M. P.; Rahmawati,; Masturi,; Bijaksana, S.; Khairurrijal,; Abdullah, M.
Abstract : Nanocomposite magnetic polymer electrolytes based on poly(vinyl alcohol) (PVA) complexed with lithium hydroxide (LiOH) and containing magnetite (Fe3 O4 ) nanoparticles were prepared using an in situ method, in which the nanoparticles were grown in the host polymer electrolyte. Ion carriers were formed during nanoparticle growth from the previously added LiOH precursor. If a high concentration of LiOH was added, the remaining unreacted LiOH was distributed in the form of an amorphous complex around the Fe3 O4 nanoparticles, thus preventing agglomeration of the nanoparticles by the host polymer. By addition of Fe3 O4 the composite polymer electrolytes improved the ionic conductivity, resulting in a maximum conductivity of 1.81 × 10 - 3 S⋅cm -1 . The magnetic properties of the polymer electrolyte were investigated through magnetic susceptibility studies, and the material was predominantly ferromagnetic.